Uso do álcool de depressão no contexto da adolescência: um estudo psicossociológico - Montanha, Henriett Marques (2013)
This thesis aimed at apprehending the social representations about alcohol use and depression elaborated by adolescent students. It was used as theoretical framework the contribution of the Social Representations Theory. The study counted on a sample of 349 professional high school students, mostly female (71.3%), aged between 13 and 17 years, with a mean of 15.8 (sd = 1.04%).The data gathering counted on the following research instruments: Free Word Association Technique- TALP (inducing stimulus: depression, depressed person, alcohol use, adolescence and myself), Biossociodemographic questionnaire, Alcohol Use Disorders Identification Test (AUDIT), Children s Depression Inventory (CDI) and semi structured interviews. The software Trideux was used to run the factorial correspondence analysis of free word associations and variables of the participants. The data obtained from the questionnaire and the AUDIT were processed by SPSS 21 and analyzed by descriptive statistics. The discourse of the participants were processed and analyzed by software ALCESTE by means of lexical analysis (standard and cross-table functions). The results obtained by the Factor Analysis output by the software Trideux showed semantic fields associated with depression and objectified by the words crying, disease, death, alone, anguish and pain; the evocations resulting from the stimulus depressed person were objectified in words: boring, sick and alone. The inducing stimulus alcohol use, the participants objectified through the elements: party, addiction and problem. The inducing stimulus adolescence the objectifications were presented by the words sex, rebellion, discovery and party. And lastly, the stimulus myself, was objectified by the participants by the words: cool, beautiful and friendly. The results from the AUDIT demonstrated good internal consistency (=0, 84); concerning the categorical analysis in 129 (36.9%) adolescents scored their answers in Zone I (Low Risk consumption), 17 (4.9%) adolescents scored in Zone II (Risk), 2 (0.6%) in Zone III (High Risk) and 1 (0.3) scored in Zone IV (Dependency). The results obtained by CDI revealed good reliability (=0, 86); being 10% of adolescents characterized with depressive symptoms, 68.6% of these students were females, indicating more frequency for the age of 15 years (30.3%). The results output by ALCESTE showed in the first lexical class, entitled Depression: concepts, causes and consequences of depression, representations objectified in feelings of sadness and other elements such as power, careless, school, love, trauma, family, suicide, suffer , loss, illness, medicine, death, among others that were anchored in psycho affective dimensions. The second lexical class, called Alcohol: concepts, causes and consequences. The participants of this class objectified the mentioned issue in the elements as: drinking beer, curiosity, friends, death, abuse, influence, party, accident, addiction, among others. Such representations are anchored in behavioral and normative dimensions of the social environment probably in their social environment. The third class output by ALCESTE entitled Adolescence: concepts and experiences included the participants who objectified this theme in: stage, life, and way, moment in time, change, choice, responsibility, rebellion, play, sex, study, adult, and discoveries, among others. The findings of this study demonstrated that 42.7% of adolescents ingested alcohol, 10% had depressive symptoms. In this sense it was not possible to associate depressive symptoms to alcohol use. However, it is believed that the results of this research are imperative to expand the reflections and changing attitudes about adolescents behaviors concerning the prevention of alcohol abuse, as well as, the mental health, and, consequently the implementation of effectively educational policies aimed at covering the health of adolescents as a whole.